While rich siphon money, poor drive economy : Prof Akash tells int'l conference in Dhaka - The Daily Star (The Daily Star, 2014)
BRAC Institute of Governance and Development (BIGD), in association with Effective States and Inclusive Development (EISD), International Growth Centre and Think Tank Initiative, organised the three-day international conference on the political economy, accountability and governance.